Investigando os fatores que influenciam o raciocínio combinatório em adolescentes de 14 anos - 8ª série do Ensino Fundamental - Esteves, Inês (2001)
The aim of this research was studying the acquisition and the development of the prime concepts about combinatory analyses among fourteen years old teenagers finishing the elementary school. In order to do this, we developed a teaching sequence based on psychological and educational theories, which belong to problem-situations through the direct county. We dealed with two groups: the experimental and the reference ones. These had done a previous test before beginning the new concept, and then studying the combinatory analyses based on two different approaches. While the experimental group did a study through a teaching sequence prepared by us, the reference group followed the traditional approach presented by didactic books. At the end both groups did a final test whose results were analyzed observing these points of view: general fulfilment of the groups and the fulfilment by items, targets and the individual one. At last, we proceeded the analyse of the behaviour among the three pairs of students from the experimental group based on their performances during the study. The results showed that the students presented troubles solving these problems. The main faillure motives were about the misunderstanding of the order combination problems; lack of organization to number systematically the data, doubts about the identification of equivalent arithmetic species and the wrong interpretation of the problem when this presented more than one stage